Correlation between non-spectral and cumulative-based ground motion intensity measures and demands of structures under mainshock-aftershock seismic sequences considering the effects of incident angles. (December 2022) - Amiri, Saeed; Di Sarno, Luigi; Garakaninezhad, Alireza
Abstract: One of the pivotal steps in seismic assessment of structures is the definition of functional relationships between an Engineering Demand Parameter ( EDP ) and a ground motion Intensity Measure ( IM ). This paper investigates the correlation between widely used non-spectral and cumulative-based ground motion intensity measures and corresponding engineering demand parameters for regular and irregular structures as bidirectional single-degree-of-freedom (2D-SDOF) systems. The correlation is investigated under sequential earthquakes in terms of efficiency and sufficiency, considering various seismic incident angles. Structural performance is expressed as maximum inelastic displacement, MD, maximum inelastic absolute acceleration, MA, residual displacement, RD, and hysteretic energy, EH . The results of extensive parametric analyses show that if the MD, MA, EH and RD of regular systems are considered as demand parameters, the optimal IMs in terms of efficiency and sufficiency are v sq, a rms, v rs and v sq, respectively.